Early Mobilization After Stroke Is Not Associated With Cognitive Outcome: Findings From AVERT. Issue 9 (September 2018) - Cumming, Toby B.; Bernhardt, Julie; Lowe, Danielle; Collier, Janice; Dewey, Helen; Langhorne, Peter; Thrift, Amanda G.; Green, Ashleigh; Mohanraj, Rajkumar; Kramer, Sharon F.; Churilov, Leonid; Linden, Thomas
Abstract : Background and Purpose—: We aimed to determine whether early mobilization after stroke affects subsequent cognitive function. Methods—: AVERT (A Very Early Rehabilitation Trial) was an international, 56-site, phase 3 randomized controlled trial, conducted from 2006 to 2015. Participants were included if they were aged 18+, presented within 24 hours of stroke, and satisfied physiological limits for blood pressure, heart rate, and temperature. Participants were randomized to receive either usual stroke unit care or very early and more frequent mobilization in addition to usual stroke unit care. The Montreal Cognitive Assessment, scored 0 to 30, was introduced as a 3-month outcome during 2008. Results—: Of the 2104 patients included in AVERT, 317 were assessed before the Montreal Cognitive Assessment's introduction. Of the remaining 1787, 1189 (66.5%) had complete Montreal Cognitive Assessment data, 456 (25.5%) had partially or completely missing data, 136 (7.6%) had died, and 6 (0.3%) were lost to follow-up. In surviving participants with complete data, adjusting for age and stroke severity, total Montreal Cognitive Assessment score was no different in the intervention (n=595; median, 23; interquartile range, 19–26; mean, 21.9; SD, 5.9) and usual care (n=594; median, 23; interquartile range, 19–26; mean, 21.8; SD, 5.9) groups ( P =0.68). Conclusions—: Exposure to earlier and more frequent mobilization in the acute stage of stroke does not influence cognitive outcome at 3 months. This stands in contrast to the primary outcome from AVERT (modified Rankin Scale), where the intervention group had less favorable outcomes than controls. Clinical Trial Registration—: URL: https://www.anzctr.org.au . Unique identifier: ACTRN12606000185561.